Cisplatin cycles treatment sustains cardiovascular and renal damage involving TLR4 and NLRP3 pathways - Antonio González; Soledad García‐Gómez‐Heras; Raquel Franco‐Rodríguez; Visitación López‐Miranda; Esperanza Herradón (Wiley, 2023)
Abstract Cisplatin is clinically proven to combat different cancers, including sarcomas, soft tissue cancers, bones, muscles, and blood. However, renal and cardiovascular toxicities are important limitations in cisplatin therapeutical use. Immunoinflammation could be key factor in cisplatin‐induced toxicity. The aim of the present study was to evaluate the activation of the inflammatory TLR4/NLRP3 pathway as a common mechanism for cardiovascular and renal cisplatin's cycles treatment toxicity. Adult male Wistar rats were treated with saline, cisplatin 2 mg/kg or cisplatin 3 mg/kg (intraperitoneally once a week, for five experimental weeks). After treatments, plasma, cardiac, vascular, and renal tissues were collected. Plasma malondialdehyde (MDA) and inflammatory cytokines were determined. TLR4, MyD88, NF‐κβ p65, NLRP3, and procaspase‐1 tissue expressions were also analyzed. Cisplatin treatment induced a dose‐dependent increase in plasma MDA and IL‐18. In cardiovascular system, an increase in NLRP3 and in cleaved caspase‐1 were observed in cardiac tissue and a moderate increase in TLR4, MyD88 appeared in mesenteric artery. In kidney, a significant dose‐dependent increase in TLR4, MyD88 and NLRP3 and cleaved caspase 1 expressions were observed after cisplatin treatments. In conclusion, cisplatin cycles provoke a low grade pro‐inflammatory systemic state. Kidney was more sensitive than cardiovascular tissues to this pro‐inflammatory state. TLR4 and NLRP3 are key pathways involved in renal tissue damage, NLRP3 is the main pathway involved in cardiac toxicity and TLR4 pathway in resistance vessel toxicity.